Peri-interventional hemodynamic management strategies for percutaneous chemosaturation of the liver in metastatic cancer - Rehn, Patrick; Tan, Benjamin; Turra, Jan; Adler, Patrick; Mayer, Philipp; Fischer, Dania; Fiedler-Kalenka, Mascha; Schmitt, Felix; Chang, De-Hua; Lichtenstern, Christoph; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich; et al. (Cancers, 2024)
Background: Hepatic chemosaturation for inoperable liver tumors is a palliative treatment option with a beneficial effect on survival. However, the procedure regularly leads to circulatory failure during the filtration phase, and hemodynamic management is challenging. Our study aimed to compare two different strategies for hemodynamic management during chemosaturation to develop hypotheses for improving patient care and reducing peri-interventional morbidity. Methods: We conducted a single-center retrospective cohort study including 66 procedures of chemosaturation between May 2016 and March 2024. Procedures were divided into two groups: group 1 was managed with norepinephrine as the only vasopressor and liberal use of hydroxyethyl starch (HES). Group 2 was managed with norepinephrine and vasopressin and the preferred use of balanced crystalloids. We compared these two groups with respect to hemodynamic parameters, laboratory values, and post-interventional complications. Results: The heart rate was highest and the mean arterial pressure (MAP) was lowest during the filtration phase in both groups (p = 0.868, p = 0.270). The vasoactive inotropic score (VIS) was significantly higher in group 2 during the filtration phase (31.5 vs. 89, p < 0.001). Group 1 received significantly more HES overall (1000 mL vs. 0 mL, p < 0.001). Lactate levels at admission to the ICU were higher in group 1 (22.9 vs. 14.45 mg/dL, p = 0.041). Platelet counts were lower in group 2 from directly after chemosaturation through day 2 (p = 0.022, p = 0.001, p = 0.032). The INR differed significantly directly after chemosaturation (1.13 vs. 1.26, p = 0.015). Overall, group 1 received significantly more blood products peri-interventionally. There were two bleedings and one ischemic stroke in the overall cohort. There was no peri-interventional mortality. Conclusions: Advanced hemodynamic management ensures low peri-interventional mortality and morbidity. High-dose vasopressors, including vasopressin and the preferred use of balanced crystalloids, are sufficient to stabilize circulatory function during chemosaturation.
Online veröffentlicht: 1. November 2024
Gesehen am 05.06.2025